The Stoppa approach versus the ilioinguinal approach for anterior acetabular fractures: A case control study assessing blood loss complications and function outcomes - ELMADAĞ, NUH MEHMET; Elmadag, M.; UZER, GÖKÇER; Guzel, Y.; Acar, M. A.; UZER, GÖKÇER; ARAZI, M. (My University, 2014)
Background: The modified Stoppa approach was introduced to manage fracture of the anterior column instead of the ilioinguinal approach to reduce morbidity. However there is no clinical evidence to confirm its efficiency. Therefore this study was designed to ascertain: (1) if the Stoppa approach versus ilioinguinal allows less blood loss, (2) if functional and radiological results are superior to that of the ilioinguinal approach, (3) if the rate of complication was different.
Keywords: Modified Stoppa